PERAN BUPATI dr. Hj. WIDYA KANDI SUSANTI, MM DALAM PERENCANAAN DAN PENGANGGARAN RESPONSIF GENDER (PPRG) PADA APBD KABUPATEN KENDAL TAHUN ANGGARAN 2011-2013 - Eraisha Valensia; Sulistyowati Sulistyowati; Lusia Astrika (Journal of Politic and Government Studies, 2015)
Gender Responsive Planning and Budgeting (PPRG) is planning and budgetingarranged by considering four aspects: access, participation, control, and benefits which areconducted equitably between women and men. Through Permendagri No. 67 in 2011, PPRGbecomes one of the tools to improve gender equality and justice in implementing the gendermainstreaming (PUG) strategy in a region.This study was conducted to determine the role of Regent Widya Kandi Susanti inplanning and budgeting the gender responsive local budgets. It also describes variousproblems in the field such as enabling and inhabiting factors both from within and fromoutside, so that the influence of women as the head of a region in gender responsive planningand budgeting to implement gender mainstreaming in Kendal Regency is known. The methodof the study used was qualitative description. Primary data source was gathered throughinterview using purposive sampling technique, while secondary data were obtained fromdocument, archive and other sources relating to the study. The analysis used qualitative dataanalysis technique by reducing data, presenting data, and drawing conclusion or verification.The research result shows that Regent Widya Kandi Susanti’s commitment in reducinggender discrepancy is written in the vision and mission of Kendal Regency RPJMD and whomore of a role in the implementing PPRG in Kendal Regency are PUG teams. The obstaclesin implementing PPRG in Kendal Regency is the existence of official rotation which is toofast, the absence of regional regulation on the implementing PPRG and the lack of publicofficial knowledge regarding gender causes PPRG has not been implemented effectively ineach SKPD, and gender responsive budget allocation in Kendal Regency Budgets year 2011-2013 remains neutral.Recommendations that can be given are Kendal Regency Government should givecommitment and support through local regulations to assure the implementation of genderresponsive budget in planning, budgeting, monitoring, and evaluating activities. Publicofficials also need to obtain gender responsive budget training sustainably in developing theappropriate understanding regarding gender responsive budget.